2017
DOI: 10.1111/cup.13082
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of a case of agminated Spitz nevi and congenital‐pattern nevi arising in extensive nevus spilus

Abstract: Nevus spilus is a melanocytic neoplasm characterized by a tan macular background punctuated by multiple hyperpigmented macules or papules that represent various types of nevi. These include junctional and compound nevi, Spitz nevi, and rarely blue nevi. We report a unique case of widespread, multiple nevi spili giving rise to agminated Spitz nevi and congenital-pattern compound nevi. We performed genetic analysis to further characterize the mutational profile of this rare entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…32 Since then, HRAS has also been recognized as a driver for nevus spilus and investigators have shown that where the HRAS gene resides. 14,16,20,24,25 Since these discoveries, much has been learned about the pathogenesis of Spitz including the fact that a significant majority of Spitz, as well as some other classes of melanocytic neoplasms such as PRKCA fusion melanocytic nevi/ tumors, are the result of genomic fusions. 20,21,[33][34][35] However, there have been very few studies investigating whether fusions can play a role in agminated presentations of melanocytic neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Since then, HRAS has also been recognized as a driver for nevus spilus and investigators have shown that where the HRAS gene resides. 14,16,20,24,25 Since these discoveries, much has been learned about the pathogenesis of Spitz including the fact that a significant majority of Spitz, as well as some other classes of melanocytic neoplasms such as PRKCA fusion melanocytic nevi/ tumors, are the result of genomic fusions. 20,21,[33][34][35] However, there have been very few studies investigating whether fusions can play a role in agminated presentations of melanocytic neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] ASN have been shown to occur in the setting of nevus spilus as a result of a mosaic HRAS mutation, involving the entire area of the nevus spilus, along with copy number gains of 11p in the focal spitzoid proliferations. 14,16,20,24,25 However, there is limited knowledge regarding the pathophysiology of ASN outside of the setting of nevus spilus, and the potential for genomic fusions to play a role in agminated nevi. 11,15,26 In this study, we present the clinical, histologic, and molecular findings of three cases of agminated melanocytic neoplasms harboring genomic fusions and therefore propose that genomic fusions can play a role in the development of agminated Spitz or other fusion-mediated melanocytic neoplasms.…”
mentioning
confidence: 99%
“…HRAS mutations have also been detected in urothelial and squamous cell carcinomas, adenocarcinomas of various origins, leukemias, and myelodysplastic syndromes (17)(18)(19). HRAS mutations in Spitz melanocytic proliferations are most commonly missense mutations involving codons 61 and 13, with the three most commonly reported mutations being Q61L (2,6,14,20), Q61R (14,(20)(21)(22)(23), and G13R (6,21,(24)(25)(26)(27)(28).…”
Section: P Amplified And/or Hras Mutated Spitz Melanocytic Proliferationsmentioning
confidence: 99%
“…In addition to solitary lesions with typical desmoplastic Spitz nevus morphology, other melanocytic proliferations with HRAS mutations and/or 11p gain have also been described, including agminated Spitz nevi with or without associated nevus spilus (25)(26)(27)(28), recurrent Spitz nevi (30), melanocytic nevi with deep penetrating nevus-like morphology (21), pseudogranulomatous Spitz nevi (31) and a combination of syringocystadenoma papilliferum, tubular adenoma and a Spitz nevus (24). Moreover, the desmoplastic Spitz nevus phenotype is not restricted to HRAS mutated lesions since rare Spitz nevi harboring ROS1, ALK or even a BRAF fusion exhibiting a desmoplastic Spitz nevus morphology have been described (2,32).…”
Section: P Amplified And/or Hras Mutated Spitz Melanocytic Proliferationsmentioning
confidence: 99%
“…Agminated Spitz nevi arise from cutaneous genetic mosaicism. Several reports 2,3 have demonstrated somatic pathogenic HRAS variants in nevus spilus-associated agminated Spitz nevi. Recently, a complex translocation involving TRPM1, PUM1, and LCK has also been implicated 4 ; however, to our knowledge, no other genetic variants of agminated Spitz nevi have been reported.…”
mentioning
confidence: 99%